Greenland, view of valley and Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. Main Valley, south end at junction with Left Valley. Background: Left Valley; mouth of its stream which has its source in shallow pond-like lake fed from streams emitting from Hisinger Glacier [Hisinger Gletscher]. See 24-F-11, 24-F-12, 24-F-5, 27-1-13 & 27-1-12. Curry-comb Peak, forming western side of Left Valley, in background. Also can be seen dimly mouth of stream of Right Valley at junction where both streams unite and form the large river-like stream in foreground.